Granisetron versus tropisetron in the prevention of postoperative nausea and vomiting after total thyroidectomy - Papadima, Artemisia (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Postoperative nausea and vomiting (PONV) are frequently encountered after thyroidectomy. For PONV prevention, selective serotonin 5-hydroxytryptamine type 3 (5-HT(3)) receptor antagonists are considered one of the first-line therapy. We report on the efficiency of granisetron and tropisetron, with that of placebo on the prevention of PONV in patients undergoing total thyroidectomy. METHODS: One hundred twenty-seven patients were divided into three groups and randomized to receive intravenously, prior to induction of anesthesia, tropisetron 5 mg, or granisetron 3 mg, or normal saline. All patients received additionally 0.625 mg droperidol. All episodes of postoperative PONV during the first 24 h after surgery were evaluated. RESULTS: Nausea visual analogue scale (VAS) score was lower in tropisetron and granisetron groups than the control group at all measurements (P<0.01) except for the 8-h measurement for tropisetron (P=0.075). Moreover, granisetron performed better than tropisetron (P<0.011 at 4 h and P<0.01 at all other points of time) apart from the 2-h measurement. Vomiting occurred in 22.2%, 27.5%, and 37.5% in granisetron, tropisetron, and control groups, respectively (P=0.43). CONCLUSIONS: The combination of the 5-HT(3) antagonists with droperidol given before induction of anesthesia is well tolerated and superior to droperidol alone in preventing nausea but not vomiting after total thyroidectomy.